Communication Patterns of Parents with Professions as a Early Years Teachers and Early Childhood in Utilizing YouTube as a Digital Literacy Media - Annisa Aurora, Cut; Sugiyo Pranoto, Yuli Kurniawati; Formen, Ali (Jurnal Penelitian dan Pengembangan Pendidikan, 2025)
The challenges in parents' monitoring and regulating digital content require effective communication patterns between parents and children. This study aims to analyze communication patterns between parents who work as PAUD teachers and early childhood in utilizing YouTube as a digital literacy medium. This study is a quantitative study with a correlational design. The study subjects were PAUD teachers with children aged 0–8 years in Semarang City. The data collection technique used a questionnaire, while data analysis was carried out through descriptive analysis and classical assumption tests, including normality tests, linearity tests, Spearman Rank correlation tests, and Wilcoxon Signed Rank One-Sample tests. The study's results showed a significant positive relationship between parent-child communication patterns and the use of YouTube as a digital literacy medium. The better and more intensive the communication pattern, the higher the success of the educational use of YouTube. The communication patterns applied, namely the equality pattern and the balanced separate pattern, reflect the active involvement of parents through mentoring, time restrictions, and control features. The conclusion of this study shows that effective parental communication patterns play a very important role in supporting early childhood digital literacy through the use of YouTube. The implication is that parents can optimize their role in guiding children to explore digital content wisely and in a balanced way.